Levels of Academic Leaders’ Emotional Intelligence, Team Emotional Climate & Team Member Job Satisfaction - MUHAMMAD ADNAN REHMAN; MUHAMMAD NAUMAN HABIB; SHAHZAD KHAN (Journal of Business & Tourism, 2021)
The study intended to examine leaders’ emotional intelligence, emotional work climate and job satisfaction among several teams of higher educational institutes. A few studies have examined the effects of these variables but seldom studies existed which examined the level of these variables. The aim of this study was to find out the difference between the true mean and the comparison value. Questionnaire survey of 30 team leaders and 120 team members was conducted. The paper applied one sample t-test using the SPSS 20 software to test the hypothesis. The study found out that there is a slight difference between the true mean and the comparison value. Although the difference is statistically significant but not large enough to be practically significant. Therefore, the subjects recruited were treated as normal.